A remonstrance of the directors of the Netherlands East India Company presented to the Lords States Generall of Vnited Provinces, in defence of the said companie, touching the bloudy proceedings against the English merchants executed at Amboyna : together with the acts of the processe against the sayd English, and the reply of the English East English Company to the said remonstrance and defence. [electronic resource] : (1632)
Summary goes here